The HAPO Study: Paving The Way For New Diagnostic Criteria For GDM - COUSTAN, Donald R (2010)
The Hyperglycemia and Adverse Pregnancy Outcome (HAPO) Study was performed in response to the need for internationally agreed upon diagnostic criteria for gestational diabetes, based upon their predictive value for adverse pregnancy outcome. Increases in each of the three values on the 75 gram, 2-hour oral glucose tolerance test are associated with graded increases in the likelihood of pregnancy outcomes such as large for gestational age, cesarean section, fetal insulin levels and neonatal fat content. Based upon an iterative process of decision making, a task force of the International Association of Diabetes in Pregnancy Study Groups (IADPSG) recommends that the diagnosis of gestational diabetes be made when any of the following three 75 gram 2-hour OGTT thresholds are met or exceeded: Fasting 92 mg/dL, one hour 180 mg/dL, two hours 153 mg/dL. Various authoritative bodies around the world are expected to deliberate the adoption of these criteria.